Epoxide-functionalized tetraethylenepentamine encapsulated into porous copolymer spheres for CO2 capture with superior stability. (15th February 2020) - Yang, Chuanruo; Du, Zhilin; Jin, Junsu; Chen, Jian; Mi, Jianguo
Highlights: The porous copolymerized beads were prepared with high hardness and toughness. The functionalized tetraethylenepentamine was encapsulated to enhance its stability. Surface crosslinking offers enhanced hydrophobicity and resistance to O2 and SO2 . The millimeter-sized beads have good capture capacity and stability in fluidization. The energy penalty for desorption is 2.15 MJ∙kg −1 (CO2 ) in CO2 -rich atmosphere. Abstract: To alleviate the global warming, various CO2 capture technologies have been developed, but most of them suffer from high energy cost, which is conflicted with their initial motivation. In order to achieve an economically efficient performance at an industrial scale, a novel porous millimeter-sized sorbent with resonable CO2 capacity is designed. The sorbent is prepared simply via suspension copolymerization of water-in-oil emulsion. Functionalized tetraethylenepentamine is encapsulated into the sorbent, which greatly maximizes amine efficiency, as the functionalized tetraethylenepentamine promotes CO2 desorption at a relatively low temperature, and maintains amine stability against oxidation and urea formation. At mean time, acrylate copolymerization and surface crosslinking ensure strong hydrophobicity of framework and surface as well as sufficient toughness against abrasion during fluidization operation. The CO2 working capacity of sorbent is 1.9 mmol∙g −1 . A rapid adsorption/desorption kinetics and long-persistent stability have been obtained under complicated atmospheric environments and fully fluidized state. The energy penalty for sorbent regeneration is 2.15 MJ∙kg −1 (CO2 ) in the presence of water, indicating a promising application prospect in CO2 capture from flue gas.